Mapping the global scientific knowledge of peste des petits ruminants virus from 1990 to 2023: Identifying research hotspots, gaps, and future directions. - Alzuheir, Ibrahim M (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: This study aims to analyze and map existing research literature on peste des petits ruminants virus (PPRV) to identify research hotspots, knowledge gaps, and future directions. PPRV causes peste des petits ruminants (PPRs) disease, leading to significant impacts on small ruminants through high mortality rates and trade limitations. Eradication programs are led by the Food and Agriculture Organization and the World Organization for Animal Health. Materials and Methods: Data were obtained from the Scopus database using keywords related to PPRV and PPR, covering the period from 1990 to 2023. Validation methods were employed to verify the search strategy’s accuracy. Data analysis focused on identifying temporal evolution, geographical distribution, key contributors, sources, research hotspots, and gaps, which were visualized using maps. Results: The study identified 478 research documents from 1,834 authors, with most being research articles (91.0%). A significant increase in publications was observed from 1990 to 2023, peaking in 2019 and 2021. India led with 112 articles, followed by the UK (79) and China (71). Top research institutions included the Indian Veterinary Research Institute and the Pirbright Institute in the UK. Major contributors like S. Parida and V. Balamurugan formed dense international collaboration networks. Key journals included “Transboundary and Emerging Diseases” and “Journal of Virological Methods.” Conclusion: This study reveals an increased global scientific production on PPRV, driven by international collaboration. However, research gaps remain, particularly from North African and Middle Eastern countries. Priorities include vaccine development, vaccination campaigns, veterinary capacity building, and enhanced reverse transcription polymerase chain reaction implementation. Insights from this study can guide policymakers, funders, and researchers in prioritizing resources and strategies to eradicate PPRV, ensuring sustainable livestock health and economic stability. J. Adv. Vet. Anim. Res., 12(1): 90–98, March 2025 http://doi.org/10.5455/javar.2025.l875